STRATEGIC IMPERATIVES OF THE DEVELOPMENT OF REGIONAL ECONOMIC SYSTEMS IN THE CONDITIONS OF THE FORMATION OF THE CREATIVE ECONOMY - KHANIN, Semen (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the main provisions of the development of the creative economy. It was substantiated that today the development of the creative economy and creative industries is the basis for ensuring competitiveness in the global environment. It was determined that the development of the creative sector is significantly influenced by the innovative capacity of regional economic systems and the state as a whole. The basis for the development of the creative economy are intellectual and innovative determinants, since it is on the implementation of creative ideas and startup projects that a new format of social ties is built. The determinants of the intellectual and innovative development of regions in the conditions of the formation of the creative economy are complex multifactorial elements that include economic, social, cultural, technological and institutional factors, which include: human capital, technological infrastructure, economic factors, socio-cultural aspects, institutional support, international cooperation, and the environmental component. The identification of determinants of intellectual and innovative development of regional economic systems made it possible to outline the strategic imperatives of the formation of a creative economy, which involve the implementation of new strategies aimed at using innovative potential, increasing competitiveness and attracting creative resources. It was determined that the creative economy is currently actively developing areas of creative industries, which include socio-cultural aspects, such as supporting art, design, architecture, cinematography, etc., which create the basis for creative industries. It was established that in conditions of economic crisis and unstable security situation, it is the support and development of small and medium-sized businesses that are the basis for supporting the economic situation in the state and regions at the expense of tax revenues to budgets of all levels, providing jobs, which contributes to reducing social tension in the regions. In conditions of general sustainable development, Ukraine, like European countries, is implementing the principles of environmental friendliness and energy efficiency in production processes.